Syllabic Keyboard: A Literacy Game for Motivating First Grade Children to Read - Guerra, Fabrício; Gorgônio, Flavius; Guerrero, Dalton; de Figueiredo, Jorge (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2019: Anais do XXX Simpósio Brasileiro de Informática na Educação, 2019)
The main purpose of this work was to conduct an experiment with a proposed technological solution - Syllabic Keyboard - in order to verify if it could impact on reading motivation related metrics in Brazilian disadvantaged 1st grade children, for their literacy issues are harmful to their general school success possibilities and motivation to read have been found to be associated with good reading achievements in further grades. Results from experimental data analysis showed positive effects from gameplay on reading motivation, taste for reading, and playing experience.